2019
DOI: 10.1021/acs.energyfuels.9b03625
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of Triamine Functionalized Silica Reinforced Polymeric Gels Developed for Conformance Control Applications

Abstract: Recently, cross-linked polymers such as polyacrylamide (PAM)/polyethylenimine (PEI) have been used in conformance control applications to replace conventional lost circulation materials (LCMs). The objective of this work is to introduce functionalized silica to reinforce PAM and enhance gel performance under high temperature high pressure (HTHP) conditions. A system was developed using PAM/triamine silica (TAS) combined with nanosilica (NS) to replace the conventional PEI as a cross-linker. Polymer systems con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Another study was conducted using nanosilica to enhance the physical stability and gel strength of PAM/TRI gelant. [ 43 ]…”
Section: Resultsmentioning
confidence: 99%
“…Another study was conducted using nanosilica to enhance the physical stability and gel strength of PAM/TRI gelant. [ 43 ]…”
Section: Resultsmentioning
confidence: 99%
“…To test this theory, NS was added to the system in an attempt to increase the stability of the colloidal system and decrease the settling rate since NS was successful in providing stability to another colloidal crosslinker in a previous study. 28 As presented in Table 2 , NS succeeded in physically stabilizing these systems where a gel was produced at conditions where the gel was not producible in the absence of NS. In addition, it has successfully decreased the separation phase at lower pH conditions.…”
Section: Resultsmentioning
confidence: 97%
“…Another factor that affects the stability of colloidal crosslinkers is the type of additives in the system where recent studies showed that silica nanoparticles can enhance both the thermal as well as physical stabilities of micro-sized particles in the polymeric solutions. 28 , 29 Apart from the stability of particles, crosslinking of the inorganic crosslinkers was found to be pH-triggered, having the gelation time decreased as the pH increases. 30 The effect of pH is believed to result from the hydrolysis of PAM that is increased at high pH, leading to the conversion of more amide groups to carboxylate groups resulting in more crosslinkable sites.…”
Section: Introductionmentioning
confidence: 99%
“…As inorganic particles generally have high thermal stability and rigidity while organic components have good flexibility, the combination of PAM and inorganic nanoparticles may endow PAM-based hydrogels with improved mechanical properties and enhanced resistances to temperature and salt. 28,29 Shamlooh 30 and Hamza 31 prepared SiO 2 −PAM composite hydrogels by combining PAM with SiO 2 and triamine silica, respectively. Silica nanoparticles are suitable for adding into hydrogel microspheres as profile control agents because of their rigidity and resistances to salts and temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…With decreasing the particle size, the oscillation energy increased, resulting in better nanofluid diffusion at the interface between the oil drop and the solid matrix. Apparently, the increase in elasticity of microspheres and the inhibition of rapid swelling of the microspheres would be beneficial for efficient profile control and plugging. As inorganic particles generally have high thermal stability and rigidity while organic components have good flexibility, the combination of PAM and inorganic nanoparticles may endow PAM-based hydrogels with improved mechanical properties and enhanced resistances to temperature and salt. , Shamlooh and Hamza prepared SiO 2 –PAM composite hydrogels by combining PAM with SiO 2 and triamine silica, respectively. Silica nanoparticles are suitable for adding into hydrogel microspheres as profile control agents because of their rigidity and resistances to salts and temperatures …”
Section: Introductionmentioning
confidence: 99%